VOTING BEHAVIOUR AMONG MALAYSIAN STUDENTS IN INDONESIA IN THE 13TH MALAYSIAN GENERAL ELECTION - Ign. Agung Satyawan; Budiarjo Budiarjo (Spirit Publik: Jurnal Administrasi Publik, 2016)
The 13th general election in Malaysia is significant momentum in Malyasian politics. The election held in March 2013 was a testing for Barisan Nasional (BN) the biggest coalition parties led by United Malays National Organization (UMNO) to win the election.  Since 1998, the votes for BN decreased but the votes for the opposition increased. If the BN lost its power in thw 13th election, it will have an impact on domestic political change. It will also bring a change in economic policy. Malaysia's political-economic changes will also take effect on the political-economic of Indonesia given the relations of economic, trade and labor has a substantial aggregate in Indonesian macro economy. The prediction of political-economic change can be seen from the behavior of the voters in 13th election. This study will examine the voting behavior of Malaysian students who are studying in Indonesia. Survey technique is used as the method in this research. In general, students do not exercise their voting rights. There is a possibility that they are reluctant to use their right to vote because most of the respondents started to not respect the country's ruling BN and also do not trust the Election Commission in conducting free and fair elections. Key words: Voting Behavior, General Election, Malaysian Political System, Political Participation